Do metal alloy primers increase the bond strength of orthodontic tubes? - Keity Cristina Moreira de Oliveira; Daylana Pacheco da Silva; Cecília Pedroso Turssi; Flávia Lucisano Botelho do Amaral; Vanessa Cavalli (Universidade Estadual de Campinas, 2019)
Aim: To evaluate the bond strength (BS) and failure mode of orthodontic tubes treated with different alloy primers at the interface among enamel, resin and orthodontic tubes. Methods: Orthodontic tubes were bonded to the enamel of 80 bovine incisors with the orthodontic resin (Transbond XT, 3M Unitek). Prior to bonding, the tubes were chemically treated with (n=20) Metal/Zirconia Primer (MZ, Ivoclar), Scothbond Universal (SB, 3M Espe); Orthoprimer (OP, Morelli) or left untreated (Control - C). Specimens were submitted to 5,000 thermal cycles (5 and 55o C) to age the bonded interface. A shear BS test and failure modes were conducted, and the results were analyzed using one-way analysis of variance and Fisher's exact test, respectively. Results: No differences were observed among groups regardless of the type of alloy primer used (p = 0.254). However, no differences were observed among the failure modes of the groups tested (p=0.694). The adhesive failure mode between the resin and enamel was the most prevalent failure (45%) for groups OP and C, whereas cohesive failure in the orthodontic resin was the most prevalent failure (40%) for groups SB and MZ. Conclusion: Alloy primers were unable to increase the BS of the orthodontic tubes to enamel.